Nurses' Practices regarding Patients Discharge Planning post Cardiac Surgery at Cardiac Centers in Baghdad city - Abdulrdha, Mustafa; Mansour, Kalida (Iraqi National Journal of Nursing Specialties, 2018)
Objective (s): to assess nurses' practices regarding discharge planning post-cardiac surgery and to find out the relationship between nurse practices and demographic characteristic (age, gander, level of education, years of experiences, and years of experiences in surgical ward). Methodology: A descriptive study was carried out at cardiac centers and hospitals in Baghdad (Ibn Al- Bitar specialized center for cardiac surgery; Iraqi center for heart disease and Ibn al Nafees hospital). For the period of 6th February 2017 up to 1st of June 2018. A non-probability (purposive) sample of (58) nurses (male & female) who were working in surgical wards. The data was collected, by using of a questionnaire, which consists of two parts, part (1) demographic data form that consists of (10) items, the part (2) that consists of (7) domains (52) items concerning nurses' practices level checklist was used to collect data from nurses. The validity of the checklist was determined by presenting it to (16) specialist experts and its reliability was determined through a pilot study. The data analysis through using descriptive statistical analysis procedures and inferential analysis procedures.Results: The study revealed that the nurses have poor practices in all aspects regarding patients discharge planning in surgical cardiac wards.Recommendations: Conduct of an educational program regarding discharge planning in order to improve nurses' practices.